Transcriptomic investigation of meat tenderness in two Italian cattle breeds. (9th February 2016) - Bongiorni, S.; Gruber, C. E. M.; Bueno, S.; Chillemi, G.; Ferrè, F.; Failla, S.; Moioli, B.; Valentini, A.
Summary: Our objectives for this study were to understand the biological basis of meat tenderness and to provide an overview of the gene expression profiles related to meat quality as a tool for selection. Through deep mRNA sequencing, we analyzed gene expression in muscle tissues of two Italian cattle breeds: Maremmana and Chianina. We uncovered several differentially expressed genes that encode for proteins belonging to a family of tripartite motif proteins, which are involved in growth, cell differentiation and apoptosis, such as TRIM45, or play an essential role in regulating skeletal muscle differentiation and the regeneration of adult skeletal muscle, such as TRIM32 . Other differentially expressed genes ( SCN2B, SLC9A7 and KCNK3 ) emphasize the involvement of potassium–sodium pumps in tender meat. By mapping splice junctions in RNA‐Seq reads, we found significant differences in gene isoform expression levels. The PRKAG3 gene, which is involved in the regulation of energy metabolism, showed four isoforms that were differentially expressed. This distinct pattern of PRKAG3 gene expression could indicate impaired glycogen storage in skeletal muscle, and consequently, this gene very likely has a role in the tenderization process. Furthermore, with this deep RNA‐sequencing, we captured a high number of expressed SNPs, for example, we found 1462 homozygous SNPs showing the alternative allele with a 100% frequency when comparing tender and tough meat. SNPs were then classified into categories by their position and also by their effect on gene coding (174 non‐synonymous polymorphisms) based on the available UMD_3.1 annotations.